2021
DOI: 10.1111/den.13907
|View full text |Cite
|
Sign up to set email alerts
|

External drainage of bile and pancreatic juice after endoscopic submucosal dissection for duodenal neoplasm: Feasibility study (with video)

Abstract: Background and Aims Endoscopic submucosal dissection (ESD) for superficial duodenal epithelial tumors (SDETs) is technically difficult and has a high risk of adverse events. Endoscopic nasobiliary and nasopancreatic duct drainage (ENBPD) may reduce the risk of delayed adverse events by preventing exposure of the post‐ESD mucosal defect to bile and pancreatic juice. This study was performed to evaluate the safety and feasibility of ENBPD after duodenal ESD. Methods Patients who underwent ESD for SDETs from July… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Figures 1 and 2 illustrate representative clip-based techniques (hold-and-drag using repositionable clip [QuickClip Pro, HX-202UR; Olympus], 83 EPSS using detachable endoloop, 85 line-assisted complete closure, 78 mucosa-submucosa clip, 17,86 underwater clip closure, 87 and E-LOC 13 ), mechanical clipping (OTSC with clips 14,38,46 ), and surgical stitch-based techniques (OverStitch 15 and EHS 10,90 ).…”
Section: Technical Illustration Of Representative Closure Techniquesmentioning
confidence: 99%
“…Figures 1 and 2 illustrate representative clip-based techniques (hold-and-drag using repositionable clip [QuickClip Pro, HX-202UR; Olympus], 83 EPSS using detachable endoloop, 85 line-assisted complete closure, 78 mucosa-submucosa clip, 17,86 underwater clip closure, 87 and E-LOC 13 ), mechanical clipping (OTSC with clips 14,38,46 ), and surgical stitch-based techniques (OverStitch 15 and EHS 10,90 ).…”
Section: Technical Illustration Of Representative Closure Techniquesmentioning
confidence: 99%
“…We analyzed clinical courses of cases with perforation of duodenal ESD and found that closing the whole area of mucosal defect as well as perforation site improved clinical outcomes. The maximum C-reactive protein value and length of hospital stay of cases where the mucosal defect was closed completely were almost equivalent to those without perforation [44] . Closing the mucosal defect enables managing the patients conservatively in the case of intraprocedural perforation as well as helps avoid delayed AE [Figure 3].…”
Section: Countermeasures For Complicationsmentioning
confidence: 80%
“…In cases where closure of the entire mucosal defect is not possible and/or when a lesion is located near the POV, insertion of endoscopic nasobiliary drainage (ENBD) and endoscopic nasopancreatic drainage (ENPD) tubes for external drainage of biliary and pancreatic juices after ESD is reportedly effective at preventing delayed bleeding and perforation. 11,12 Therefore, a bile duct stent and pancreatic duct stent were placed before treatment to improve lesion visualization and avoid ductal injury during ESD. The stents also facilitated the insertion of ENBD and ENPD tubes after resection (Fig.…”
Section: Casementioning
confidence: 99%